Planning volume supply material resources in construction - O. V. Demidenko; N. E. Alekseev (Вестник СибАДИ)
The organizational and technological issues of the transport documents provide material resources construction projects considered without sufficient justification. In the article the task of planning the volume of deliveries agreed with the construction company's internal capabilities and external conditions is formulated in the form of a mathematical model of linear programming. The principles of planning, the concept of the quality of the plan, formalized internal and external constraints on the choice plan. Model developed by the authors plan will improve the level of organization of construction management flows, ensure the continuity and uniformity of the work of production and consumption of materials, products and structures.